Larry Golsh - DeWald, Louise; Buchanan, Roger (New Mexico Magazine, 1977)
This article is about Larry Golsh a Cherokee artist and his jewelry creations.
4 paged/double sided New Mexico Magazine article
Master list item #: 21
File location is in the New Mexico file Cabinet
Keywords: Golsh, Larry; Indian Jewelry; Indian Artist; Indian Art; Cherokee Indians; Arizona; New Mexico